Prevalence and determinants of external injuries among industrial workers in an urban area of Kancheepuram district, Tamil Nadu - C., Sashidharan; P., Mohan Kumar; S., Gopalakrishnan (International Journal Of Community Medicine And Public Health, 2017)
Background: Workers engaged in industries and construction sites faced several problems and often work in substandard conditions, getting exposed to various hazards in the work place without appropriate safety training. Injuries among workers are an important health issue in industries. This study was planned to assess the prevalence of external injuries among industrial workers in an industrial area and to identify the association between socio-demographic risk factors and external injuries among the industrial workers. Methods: This community based cross-sectional descriptive study was carried out in an urban area of Kancheepuram District. A sample size of 302 was calculated based on a previous study result and Probability Proportional to Size sampling was used to select the required number of workers from the four sites identified. A structured questionnaire was used for data collection. Data analyzed by using SPSS version 21. Descriptive and Analytical Statistical calculations were done. Results: This study shows that 44.3% workers were affected by some form of external injuries during their working time. Skin Injuries like abrasions and lacerations [43%], contusion [26%], cut injuries [16%], foreign body in the eyes [12%] and falling from a height [10%] were common. There was strong statistically significant association with the occurrence of external injuries in the work place with the habits of smoking and tobacco use, alcohol drinking and the nature of work among the study group. Conclusions: The study shows high prevalence of external injuries among the workers. They need to be properly trained in safety mechanisms and procedures to follow in work places and also wearing proper personal protective devises during the working hours to prevent such injuries.